Can oxygen vacancies in ceria surfaces be measured by O1s photoemission spectroscopy?. (27th April 2022) - Bosio, Noemi; Schaefer, Andreas; Grönbeck, Henrik
Abstract: X-ray photoemission spectroscopy is a standard technique for materials characterization and the O 1s binding energy is commonly measured for oxides. Here we use density functional theory calculations to investigate how the O 1s binding energy in CeO2 (111) is influenced by the presence of oxygen vacancies. The case with point vacancies in CeO2 (111) is compared to complete reduction to Ce2 O3 . Reduction of CeO2 by oxygen vacancies is found to have a minor effect on the O 1s binding energy. The O 1s binding energy is instead clearly changed when the character of the chemical bond for the considered oxygen atom is modified by, for example, the formation of OH-groups or carbonates.